STRATEGI PEMERINTAH DALAM PENGEMBANGAN POTENSI MASYARAKAT PENGRAJIN TENUN - Asa, Rikardus; Suprojo, Agung; Purwatiningsih, Annisa (Collegium Studiosum Journal, 2023)
This research aims to find out how the government's strategy in developing the human resource potential of weaving craftsmen in Kufeu Village, the process or stages carried out by the government in developing the potential of the weaving craftsmen community in Kufeu Village, as well as the inhibiting factors and supporting factors of the government in developing the weaving craftsmen community in Kufeu Village. This research uses a qualitative approach with 3 (three) resource persons selected proposiv sampling. Data in this study were obtained through interviews, observation and documentation and then analyzed qualitatively with an interactive analysis model, namely data reduction, data presentation and conclusion drawing. The results in this study show that the Government's strategy in developing the potential of the weaving artisan community in Kufeu Village, Io Kufeu District, Malacca Regency has not been able to develop as to increase the potential of the weaving artisan community, but it has been very maximum if the purpose of the government's strategy in developing the potential of the weaving artisan community in Kufeu Village is only limited to maintaining weaving as a village identity.